Linked color imaging confers benefits in profiling H. pylori infection in the stomach - Sun, Xiaotian; Bi, Yiliang; Nong, Bing; Hu, Duanmin; Sun, Xiaomin; Chen, Honglei; Xu, Yang; Liu, Yan (Endoscopy International Open, 2019)
Background and study aims There is a high prevalence of Helicobacter pylori infection. White light endoscopy (WLE) can be used for evaluating the mucosal lesions, but it does not have high diagnostic efficiency. Linked color imaging (LCI) is a newly developed endoscopic imaging technique. The aim of this study was to compare LCI with WLE in detecting and staging H. pylori infection in the stomach in a randomized controlled clinical trial.Patients and methods A total of 253 patients who had indications for gastroduodenoscopy were enrolled and randomized into Group A (n = 127), who underwent WLE followed by LCI, and Group B (n = 126), who underwent LCI followed by WLE. Clinical data were collected and the diagnostic accuracy of WLE and LCI was calculated and compared.Results The overall diagnostic accuracy of WLE and LCI for H. pylori infection was 31.5 % (n = 40) and 50.4 % (n = 64) in Group A (P = 0.001), and 36.5 % (n = 46) and 49.2 % (n = 62) in Group B (P = 0.029). In both groups, LCI had higher sensitivity, specificity, and Youden index scores than WLE. Four stages were defined in the course of H. pylori infection in the stomach. LCI staging results were more highly consistent with pathological staging than were WLE staging results (kappa value 0.772 vs. 0.516). The LCI observations were closely correlated with the pathology.Conclusion LCI had a higher diagnostic efficacy for H. pylori infection in the stomach. Endoscopic color features under LCI can help to stage and profile H. pylori-associated gastritis.